Mapping of potential storages and rainwater harvesting sites in arid region of Indus Basin using analytical hierarchy technique - Hafeez, Mohsin; Cheema, Muhammad Jehanzeb Masud; Liaqat, Umar Waqas; Amin, M.; Usman, M. (Springer, 2025)
Water, an essential element for rainwater harvesting (RWH), plays a pivotal role in addressing water scarcity and enhancing community resilience. This study conducted a comprehensive analysis of water storage in the Pothowar region, which spans approximately 23,204 square kilometers across five districts: Islamabad, Rawalpindi, Chakwal, Attock, and Jhelum. The objective was to assess the availability, demand, and utilization of water reservoirs using GIS technology to identify potential storage sites. The study utilized advanced tools, starting with the acquisition of a 12.5 m Digital Elevation Model (DEM) from ALOS PALSAR, followed by data refinement using the Fill tool. Flow direction analysis and watershed delineation in ArcGIS 10.8.2 revealed 6,508 sub-watersheds and outlets. An Analytical Hierarchy Process (AHP) model was employed to assign weights to factors such as soil, land use, rainfall, stream order, drainage density, and slope, enabling the classification of suitability classes. The results indicated that 41% of the region was classified as moderately suitable, with 3.79% rated as very highly suitable, 44.81% as highly suitable, and 10.40% as not suitable. Specific mini dam sites were proposed based on suitability, with 121 outlets classified as very highly suitable, 3,655 as highly suitable, 2,188 as moderately suitable, and 690 as not suitable. This comprehensive analysis enhances the understanding of the region’s hydrological dynamics, supporting informed decision-making for sustainable water resource management aligned with both developmental and environmental objectives. By combining advanced geospatial tools and a collaborative approach, this study offers a cutting-edge framework for regional water resource management.